Monitoring of the Wild Boar (Sus Scrofa Linnaeus, 1758), Distributed in the Territory Of Karakalpakstan - M.Sh. Toremuratov; G.K. Nurabullaeva; Q.Q. Esemuratov; B.K. Dauletmuratova (Zien Journals, 2024)
This article presents monitoring of the distribution of the wild boar population in Karakalpakstan. As a result of research work, it was established that wild boars are widespread in the Lower Amu Darya delta, around natural lakes and artesian wells in the north-west of the Kyzylkum, as well as in areas between the cracks of the Northern Ustyurt plateau and the Aral Sea
Keywords: Wild boar; habitat; population; Karakalpakstan